Using B4C Nanoparticles to Enhance Thermal and Mechanical Response of Aluminum - Fareeha Ubaid (14151129) (2017)
In this work, Al-B4C nanocomposites were produced by microwave sintering and followed by hot extrusion processes. The influence of ceramic reinforcement (B4C) nanoparticles on the physical, microstructural, mechanical, and thermal characteristics of the extruded Al-B4C nanocomposites was investigated. It was observed that the density decreased and porosity increased with an increase in B4C content in aluminum matrix. The porosity of the composites increased whereas density decreased with increasing B4C content. Electron microscopy analysis reveals the uniform distribution of B4C nanoparticles in the Al matrix. Mechanical characterization results revealed that hardness, elastic modulus, compression, and tensile strengths increased whereas ductility decreases with increasing B4C content. Al-1.0 vol. % B4C nanocomposite exhibited best hardness (135.56 Hv), Young’s modulus (88.63 GPa), and compression/tensile strength (524.67/194.41 MPa) among the materials investigated. Further, coefficient of thermal expansion (CTE) of composites gradually decreased with an increase in B4C content. Other Information Published in: Materials License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/ma10060621